Adoption factors of RFID in a voluntary environment: An empirical investigation from Australian livestock industry - Hossain, Mohammad; Quaddus, Mohammed (Australian and New Zealand Marketing Academy, 2011)
The objective of this study is to investigate the contributing factors for Radio Frequency Identification (RFID) adoption in a voluntary setting. Adopting a mixed method consisting both qualitative and quantitative approaches, the findings of this study reveals that external pressure, RFID costs, and management attitude toward RFID are the main factors to intend to adopt RFID. Moreover, expectations from RFID use are significantly important for its adoption.